Versatile Raman fiber laser for sodium laser guide star. Issue 6 (28th July 2014) - Zhang, Lei; Jiang, Huawei; Cui, Shuzhen; Hu, Jinmeng; Feng, Yan
<x xml:space="preserve">Abstract</x> A high power 589 nm laser based on Raman fiber amplifier is reported here, which works in both continuous wave and pulsed format. In the continuous wave case, the laser produces more than 50 W output. The same laser produces pulses with tunable repetition rate and duration with peak power of 84 W. The laser emits a sideband at 1.71 GHz away from the main laser frequency for better sodium excitation. The versatility of the laser offers much flexibility in laser guide star application. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>